Probing tqZ anomalous couplings in the trilepton signal at the HL-LHC, HE-LHC, and FCC-hh *Supported by the Foundation of the Henan Institute of Science and Technology (2016ZD01), part by the NExT Institute and the STFC CG (ST/L000296/1). (April 2021) - Liu 刘, Yao-Bei 要北; Moretti, Stefano
Abstract: We investigate the prospect of discovering the Flavour Changing Neutral Current (FCNC) couplings via two production processes yielding trilepton signals: top quark pair production with one top quark decaying to the Z boson and one light jet and the anomalous single top quark plus Z boson production process . We study these channels at various successors of the Large Hadron Collider (LHC), i.e., the approved High-Luminosity LHC (HL-LHC) as well as the proposed High-Energy LHC (HE-LHC) and Future Circular Collider in hadron-hadron mode (FCC-hh). We perform a full simulation for the signals and the relevant Standard Model (SM) backgrounds and obtain limits on the Branching Ratios (BRs) of, eventually yielding a trilepton final state through the decay modes and . The upper limits on these FCNC BRs at 95% Confidence Level (CL) are obtained at the HL-LHC with TeV and 3 ab −1, at the HE-LHC with TeV and 15 ab −1, and at the FCC-hh with TeV and 30 ab −1 .